Reconstructing Kenya’s Educational Philosophy to steer attainment of the Sustainable Development Goals and Kenya’s Vision 2030 Plan (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Philosophy of education in Kenya needs to be constantly reconstructed given the emerging needs of society and in light of global trends. Changes in the education system over time have not eradicated education challenges that result in unemployment and social evils in Kenya. There are also global and national goals to be met. The objective of this study was to examine the role of philosophers and suggest whether professional philosophers could reconstruct philosophy of education in Kenya to guide the achievement of Sustainable Development Goals (SDGs) and the Kenya Vision 2030 Plan. The SDGs and Kenya’s Vision 2030 work in tandem, and if effectively and efficiently implemented, guided by a sound philosophy of education, lives of all Kenyans would be raised to international standards. This study was conducted as desk research that employed critical conceptual philosophical literature review. A recommendation was made that experts in philosophy of education could use Dewey’s philosophy of pragmatism to facilitate the reconstruction of Kenya’s national philosophy of education as a tool to steer attainment of the Sustainable Development Goals and the Kenya Vision 2030.
Keywords: Sustainable Development Goals (SDGs); Kenya Vision 2030; philosophy; Dewey’s pragmatism; philosophy of education